STUDI PERBANYAKAN TUNAS PUCUK ASTER CINA (Callistephus chinensis) DENGAN PENAMBAHAN PUPUK DAUN DAN AIR KELAPA SECARA KULTUR IN VITRO - Miranty Trinawaty; Rostian Nafery (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2016)
China aster plant is a popular ornamental plant species in Indonesia, because aster has a beautiful flower with a wide range of colors such as purple, white, yellow, red, etc. Aster plant as an ornamental plant is quite attractive, but the seed supply is limited due to many factors inhibiting the cultivation techniques, so the availability of aster seeds in the field is quite limited. Plant propagation using in vitro culture technology represents a major opportunity to produce seedlings in a short time and the number of lots. This research used Randomized Completely Block Design (RCBD) with five treatments and five replications with each treatment used 5 units bottle culture samples so totally there were 125 units. The treatment of the research were: H0 (control), H1 (1.5 g Growmore + 30% Coconut Milk), H2 (1.5 g Growmore + 40% Coconut Milk), H3 (2 g Hyponex + 30% Coconut Milk) and H4 (2 g Hyponex + 40% coconut Milk). Parameters observed were: the time to sprout, shoot height, the time to form roots, number of roots and root length. The result showed that the analysis of variance was no significant effect to all parameters observed. Meanwhile, based on the tabulated results showed that the treatment H0 gave the best response to time to sprout, shoot height, time to grow roots and root length.Keywords: Aster China, Foliar Fertilizer, Coconut Water